PENGARUH KEADILAN KOMPENSASI TERHADAP KEPUASAN KERJA DAN KINERJA PEGAWAI - Hidayat, Rizki Muslim; Tjahjono, Heru Kurnianto; Fauziyah, Fauziyah (Jurnal Bisnis : Teori dan Implementasi, 2017)
An employee whose has a good performance can help the organization in achieving its intended purpose organizations lead to improvements in public services. Performance of employees, especially in the Civil Registry Office has become problems being discussed by the public (citizen of Tanah Bumbu district) because it concerns on the public service. Based on the phenomenon that occurs low performance caused by the effect of compensation justice such as Distributive Compensation Justice, Procedural Compensation Justice and job satisfaction.The object of this study is Civil Registry Office in Tanah Bumbu and the subjects are all of the employees whose work in the Civil Registry Office in Tanah Bumbu. This research uses quantitative descriptive analysis approach. The data were collected through observation, questionnaire and interview, then the data was analyze using descriptive analysis and Structural Equation Modeling (SEM) by using smart software Partial Least Squares (PLS).The results of the study showed that Distributive Compensation Justice and Procedural Compensation Justice had a significant influence on job satisfaction. Job satisfaction, Distributive Compensation Justice and Procedural Compensation Justice also had a significant influence on employees’ performance. According to the research results above, it is suggested to the Civil Registry Office of  Tanah Bumbu, in order to improve the performance of the employees especially on the variable of  Distributive Compensation Justice and Job satisfaction by implementing wage distribution and promotion system which is fair and transparent to the employees so they are satisfied and it can create better performance of the employees.